A New Class of Blue‐LED‐Excitable NIR‐II Luminescent Nanoprobes Based on Lanthanide‐Doped CaS Nanoparticles. (5th June 2019) - Zhang, Meiran; Zheng, Wei; Liu, Yan; Huang, Ping; Gong, Zhongliang; Wei, Jiaojiao; Gao, Yu; Zhou, Shanyong; Li, Xingjun; Chen, Xueyuan
Abstract: Lanthanide (Ln 3+ )‐doped luminescent nanoparticles (NPs) with emission in the second near‐infrared (NIR‐II) biological window have shown great promise but their applications are currently limited by the low absorption efficiency of Ln 3+ owing to the parity‐forbidden 4f→4f electronic transition. Herein, we developed a strategy for the controlled synthesis of a new class of NIR‐II luminescent nanoprobes based on Ce 3+ /Er 3+ and Ce 3+ /Nd 3+ co‐doped CaS NPs, which can be effectively excited by using a low‐cost blue light‐emitting diode chip. Through sensitization by the allowed 4f→5d transition of Ce 3+, intense NIR‐II luminescence from Er 3+ and Nd 3+ with quantum yields of 9.3 % and 7.7 % was achieved, respectively. By coating them with a layer of amphiphilic phospholipids, these NPs exhibit excellent stability in water and can be exploited as sensitive NIR‐II luminescent nanoprobes for the accurate detection of an important disease biomarker, xanthine, with a detection limit of 32.0 nm . Abstract : Neuartige NIR‐II‐Nanosonden, die mit einem blauen LED‐Chip angeregt werden können, wurden basierend auf der effizienten Energieübertragung von Ce 3+ auf Er 3+ und Nd 3+ in CaS‐Nanopartikeln mit Quantenausbeuten von bis zu 9.3 % und 7.7 % für Er 3+ bzw. Nd 3+ entwickelt. Die phospholipidbeschichteten CaS:Ce 3+, Er 3+ ‐Nanosonden wurden für den empfindlichen und spezifischen Nachweis des Krankheitsbiomarkers Xanthin verwendet.